Language, Gender, and Crime: Representing Female Perpetrators in Indonesian Digital News - Ernanda (Masyarakat Linguistik Indonesia, 2026)
The way media represent female perpetrators can reveal the extent to which gendered norms and expectations influence news reporting in Indonesia. The way news is framed can shape public perception of female criminals. This study aims to examine how female perpetrators are represented through social actor choices in Indonesian digital crime news. It employs a Critical Discourse Analysis approach using the Social Actor Network framework introduced by van Leeuwen. The data source of this study is the digital media detikcom. The corpus consists of 20 criminal news texts published in 2025-2026. The findings of this study show that female perpetrators in Indonesian digital media are represented through the strategies of Classification, Activation, and Exclusion. The gender identity of female criminals is highly foregrounded in news texts through the use of Classification. Through Activation, criminal acts committed by women are made explicit without the use of linguistic hedging. Exclusion is used to remove actors from the text, though its impact is not severe since female perpetrators are clearly identified elsewhere in the same texts. These strategies position female criminals as deviant social actors in Indonesian crime news, as their behavior is judged against prevailing gendered norms. Theoretically, this study reveals the linguistic mechanisms underlying the representation of female perpetrators through the Social Actor Network in the context of Indonesian digital media. Accordingly, media outlets in Indonesia need to reflect on how their linguistic choices shape the gendered representation of female perpetrators.